The public library in a multimedia society: copy, test, disseminate - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2012)
The generation of new multimedia content that facilitates contact with mobile devices is a pending task for cultural agents. From the perspective of the public library, we take augmented reality as an example and the video game industry as a reference to demonstrate some possible actions.